SPEECH STYLE USED IN THE MOVIE OF TENDANGAN DARI LANGIT - PARAMITA, SELIA NASTITI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Speech style, Tendangan Dari Langit movie, Wahyu.This study analyses the speech styles in some utterances used by the main character in the movie Tendangan Dari Langit. The writer applies Joos (cited inBroderick,1976) as a main theory and Chaer and Agustina (2010) as the supporting theory. There are two problems of the study to be solved. They are to find out the types of speech style and the speech styles which are mostly used by Wahyu in The Movie Tendangan Dari Langit.In this study, the writer used qualitative approach with document or content analysis. The writer analyzed the utterances stated by Wahyu. Then, the writer analyzed the types and the mostly used types by Wahyu based on script of the movie.Related to the first problem, the writer found that Wahyu used all types of speech style in his daily conversation. There are 2 utterances considered as Frozen style, 1 utterance considered as Formal style, 5 utterances considered as Consultative style, 79 utterances considered as Casual style and 32 utterances considered as Intimate style. Also, the writer found that out of 5, there are only 2 types of speech style as the most used by Wahyu. The first is casual style and the second is intimate style. From 118 utterances, there are 79 utterances considered as Casual style and 32 utterances considered as Intimate style.The writer suggests to use another  theory of speech style, for example nababan. The other theory like Dr. P. W. J. Nababan (1987) would help the next researchers to conduct the study of speech style in terms of enrich the theory. Then, uses English movie as the subject of the study. Also, the writer suggests to conduct the study of speech style based on novel or short story.